Cognitive reserve and dementia risk management in people with an intellectual disability. - Mc Carron, Mary; Mc Glinchey, Eimear (My University, 2023)
Dementia risk is elevated in people with intellectual disability, particularly for those with Down syndrome Differences in lifestyle factors have been cited as factors that exacerbate dementia risk in people with intellectual disability Lifestyle factors can be targeted to enhance cognitive reserve and reduce dementia risk for people with intellectual disability
PUBLISHED
Keywords: Brain health; Cognitive reserve; Dementia; Down syndrome; Intellectual disability; Resilience; Ageing; COGNITIVE AGEING; DEMENTIA; dementia risk management